Drug repurposing clinical trials in the search for life-saving COVID-19 therapies; research targets and methodological and ethical issues - Francisco José Roma Paumgartten; Isabella Fernandes Delgado; Luciana da Rocha Pitta; Ana Cecilia Amado Xavier de Oliveira (Fundação Oswaldo Cruz (FIOCRUZ), 2020)
Introduction: So far, there is no vaccine, nor are there effective drugs to treat COVID-19, an emerging viral respiratory infection deadlier than influenza. Objective: To take a snapshot picture of planned and ongoing clinical research addressing drugs potentially useful for treating SAR-CoV-2 infections. Method: A search was conducted (20 April 2020) in an international registry of clinical studies (https://ClinicalTrials.gov, US NIH). After excluding observational studies and other interventions that fell outside the scope of this study, 294 research protocols (out of 516 retrieved protocols) were selected for analysis. Results: Of 294 included trials, 249 were Randomized Controlled Trials (RCT), 118 of which were double-, triple- or quadruple-blinded studies. The interventions (drug therapies) were compared with "standard-of-care" (SOC) or with the placebo plus SOC, or yet with presumed "active" comparators. RCT focused on the primary treatment of the disease (inhibitors of viral replication) or on the therapy for resolution of hyperinflammation in pneumonia/Acute Respiratory Distress Syndrome (ARDS) and thromboembolism associated with SARS-CoV-2. The trials found in the database involve existing antiviral compounds and drugs with multiple modes of antiviral action. Antiparasitic drugs, which inhibited viral replication in cell-culture assays, are being tested as well. Regarding the adjunctive immunomodulatory, anti-inflammatory and antithrombotic therapies, a number of drugs with distinct pharmacological targets are under investigation in trials enrolling patients with severe COVID-19. Conclusions: Although many clinical studies of drugs for COVID-19 are planned or in progress, only a minority of them are sufficiently large, randomized and placebo-controlled trials with masking and concealment of allocation. Owing to methodological limitations, only a few clinical trials found in the registry are likely to yield robust evidence of effectiveness and safety of drugs repurposable for COVID-19.